Practical Guidelines to Legal Writing for Young Researchers and Professionals - Zerari, Fathi (UAE university Journal of Law, 2024)
Research about the law requires a degree of mastery of both the existing knowledge about the topic of research and the necessary methodological tool-kit to communicate the analysis and the findings to the targeted audience. This paper aims to provide young researchers and professionals in law with a step-by-step guide to write different types of legal writings. This research starts from the assumption that well situating the topic of the research within an appropriate context and adopting an adapted analysis condition a cogent structure that reflects the degree of consistency between the research gap and the aim of the research, on the one hand, and the findings and the recommendations, on the other.